Upaya Meningkatkan Motorik Halus Anak dengan Kegiatan Menggunting di TK-IT Mutiara Global - Ayu Lestari; Seprini Yuspiati; Aryuliza Aryuliza (Jurnal Pendidikan Tuntas, 2023)
This research is motivated by the low fine motor skills of Group B children at TK-IT Mutiara Global in Kualu Village. One solution to address this issue is to implement cutting out activities. Thisstudy aims to improve fine cognitive in Group B at TK-IT Mutiara Global in Kualu Village. The research method used in this study is Classroom Action Research (CAR). This classroom action research was conducted in two cycles, with two meetings in each cycle. Data collection techniques used were observation and documentation. The results of this research show an improvement in children's scores from the pre-action phase, Cycle I, to Cycle II, which can be described as follows: In the pre- action phase, 0 children or 0 % had high scores, then in Cycle 1, this decreased to 2 children or 13,3%, and in Cycle II, it became 8 children or 53,3%. The moderate score in the pre-action phase was 4 children or 26,6%, then in Cycle 1, it became 6 children or 40,0%, and in Cycle II, it became 7 children or 46,6%. The average in the pre- action phase was 7 child or 46,6%, then in Cycle 1, it became 5 children or 33,3%, and it remained at 0 children or 0% in Cycle II. The failing grade in the pre-action phase was 4 child or 26,6%, then in Cycle 1, it became 2 children or 13,3%, and in the end, in Cycle II, it increased to 0 children or 0%. Key words: fine motor skills, Cutting off, classroom action research